Food security in Latin America during the COVID-19 pandemic: A comparative study of policy responses in Mexico, Brazil, and Colombia - Contreras Peralta, Jorge (2026)
The COVID-19 pandemic revealed and worsened structural weaknesses in Latin America’s food systems, causing a sharp increase in food insecurity. This study compares how Mexico, Brazil, and Colombia responded, using a multiple case study approach within a most similar systems design (MSSD). It analyzes quantitative data from organizations like FAO, ECLAC, and WFP, applying a human rights-based framework to evaluate each country’s protection of the right to food before, during, and after the pandemic. Findings show notable differences: Brazil sustained key social programs, Mexico cut food-related budgets, and Colombia implemented decentralized responses. These variations highlight the importance of institutional design, public policy focus, and state capacity in shaping food security outcomes during health crises.